Interobserver variability of assessing body condition scores and muscle condition scores in a population of 43 active working explosive detection dogs - Christie, Kimberly M.; Barnhard, Jennifer A.; Otto, Cynthia M.; Mallikarjun, Amritha; Wilson, Clara; Levine, David; Tringali, Ashley A.; Payne, Chelsea E.; Langenbach, Anke; Brunke, Matthew W. (Frontiers in Veterinary Science, 2024)
ObjectivesThis study aimed to evaluate the agreement between explosive detection dog (EDD) handlers and a team of veterinarians in assessing body condition score (BCS) and muscle condition score (MCS), hypothesizing significant BCS differences between handlers and veterinarians, and no significant MCS differences in healthy active duty EDDs.MethodsThis prospective study analyzed variance and inter-rater intraclass correlation coefficients (ICC) of agreement within BCS and MCS assessments collected from the 43 EDDs by four blinded graders; the EDDs’ respective handler and three veterinarians with varying levels of veterinary expertise.ResultsThe results of the study showed that 74.4% of the EDD population was graded as ideal BCS (4 or 5 out of 9) by the handlers compared to 67.44% by the members of the veterinary team; however, the graders scored different subsets of individual EDDs as ideal. Normal MCS (3 out of 3) was assessed in 86.05% (n = 37) of EDDs by the handlers versus in 70.54% by the veterinary team.ConclusionThis study highlights the importance of standardized training and guidelines for BCS and MCS assessments in working dogs to improve agreement between all members of the healthcare team.